Skin cancer prevention in annual performance of total skin examination, photoprotection counseling, and patient instruction of self‐skin examination. (18th October 2013) - Yiannias, James A.; Laman, Susan D.; Stevens, Ryan; Rkein, Ali M.; Nelson, Evan; Noble, Brie N.
Abstract Background Prevention of skin cancer includes early diagnosis and photoprotection, such as by physician‐performed total skin examination (TSE) and patient‐performed self‐skin examination (SSE). Hypothesizing that 90% of our patients receive an annual TSE, photoprotection counseling, and SSE instruction, we assessed the extent to which this was documented in patients' records. We also sought to identify differences in documentation of TSE, photoprotection counseling, and instruction on SSE with or without use of a dictation template prompting documentation. Materials and methods Retrospective review of a random sample of 400 patients in an outpatient dermatology practice of a tertiary care academic medical center for any dermatology appointment between May 1 and July 31, 2007. Exclusion criteria included refusal to undergo TSE, lack of access to skin (e.g. wheelchair‐bound or in cast), or inappropriate visit type (e.g. for acne, psoriasis, or lupus). Results Of 400 randomly selected patients, 313 met inclusion criteria. The dictation template was used in 133; of these, 89% (119/133) had documentation in their clinical note of a TSE (exclusive of the buttocks or groin area), and 98% (130/133) had documentation of instruction on sun protection and SSE. Without use of the dictation template, these percentages dropped to 78% (140/180) and 20% (36/180), respectively. Physicians using a dictation template were more likely to document having conducted a TSE and instructed patients on photoprotection and SSE. Conclusions A dictation template aids documentation of annual TSE and patient education efforts on photoprotection and SSE.